Los aspectos lingüísticos de un diccionario latino - Magallón García, Ana Isabel (2002)
This article is proposing a scientific reflection on some important linguistic aspects involved in the lexicographic process. As the mere comparative study of the linguistic system in the most consulted bilingual Latin dictionaries reveals, there are practical differences in the setting-up of lemmas adopted by each one. This has been the result of the total lack hitherto of a theory considering aspects of lemmatization and organization of acceptions (i.e. the formal layout of articles) in the field of Latin lexicography.
Keywords: Lengua latina; Diccionarios; Lingüística